OCCULT HBV-INFECTION (CLINICAL REPORT) - I. A. Gabdrakhmanov; K. V. Kozlov; K. V. Zhdanov; D. A. Gusev; A. V. Semenov; Yu. V. Ostankova; V. S. Sukachev; D. M. Shakhmanov; S. S. Zhabrov; I. M. Yurkaev; G. A. Zhanarstanova; T. M. Zubik; et al. (Журнал инфектологии, 2017)
.